A novel approach for Technetium-99m radioisotope transportation and storage in lead-free glass containers: A comprehensive assessment through Monte Carlo simulation technique - Şen BAYKAL, Duygu (International Journal of Computational and Experimental Science and Engineering, 2024)
The primary aim of this project is to develop glass containers that are free from lead for the transportation of Tc-99m. The analysis included glass container structures characterized by the chemical formula 60B2O3-(25-x)GeO2-15BaO-xWO3 (where x ranges from 0 to 25). The rates of addition, in theory, range from 3.397 to 4.124 g/cm3. To evaluate the radiation shielding abilities of glass containers, the Phy-X/PSD software was used. The energy values employed in the evaluation varied from 0.015 MeV to 0.15 MeV, a range frequently employed in the field of medical physics. The transmission factors for the specific gamma energy of Tc-99m were determined using the Monte Carlo method MCNPX (version 2.7.0). The method simulates the motion and interaction of particles. The G6 glass container type exhibited the highest level of gamma-ray attenuation among all the investigated glass containers, primarily due to its superior shielding properties. The creation of glass containers that do not contain lead and are designed to contain the movement of Tc-99m has significant implications in the areas of radiopharmaceuticals and medical diagnostics. In light of the continuous attempts of the scientific community, it is advisable to undertake more investigations aimed at enhancing the technology of lead-free glass.